Lithium ion battery electrolyte and application thereof

By using additives such as diethyl cyanomethyl phosphate and lithium tetrafluoroborate in the lithium-ion battery electrolyte, combined with lithium difluorosulfonimide, the corrosion problem of LiFSI on aluminum foil current collectors has been solved, and the lithium-ion battery has been improved Cycling and fast charging performance.

CN119481277AActive Publication Date: 2025-02-18ENVISION RUITAI DYNAMICS TECH (SHANGHAI) CO LTD +1
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411598015.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-08
Publication Date
2025-02-18
Estimated Expiration
2044-11-08

AI Technical Summary

Technical Problem

In high voltage battery systems, FSI-ions in LiFSI will corrode the aluminum foil, affecting the performance and life of lithium-ion batteries, and limiting the commercial application of LiFSI.

Method used

Provided is a lithium-ion battery electrolyte containing a non-aqueous solvent, lithium difluorosulfonimide and additives, wherein the first additive is diethyl cyanomethyl phosphate and the second additive is lithium tetrafluoroborate, through these components The combination can effectively prevent corrosion of the aluminum foil current collector and improve the circulation performance of the battery.

Benefits of technology

This electrolyte effectively prevents LiFSI from corrosion on aluminum foil current collector, improves the long cycle life of lithium-ion batteries, and improves fast charging performance by reducing DC impedance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005127544420000151
    Figure BDA0005127544420000151
  • Figure BDA0005127544420000161
    Figure BDA0005127544420000161
Patent Text Reader

Abstract

The invention provides a lithium ion battery electrolyte and application thereof. The electrolyte comprises: a non-aqueous solvent; the lithium salt comprises lithium bis (fluorosulfonyl) imide; and an additive, the additive comprising a first additive, and the first additive comprising diethyl cyanomethylphosphonate. According to the lithium ion battery electrolyte and the application thereof provided by the invention, the corrosion of an aluminum foil current collector can be effectively prevented, the gas production performance of a lithium ion battery is improved, and the cycle performance and the quick charge performance of the battery are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of power batteries, and in particular to a lithium-ion battery electrolyte and applications thereof. Background Art

[0002] With the increasing requirements of the new energy vehicle industry for the energy density of new energy batteries and the development of high nickel content in cathode materials, it is difficult for lithium hexafluorophosphate (LiPF6) to fully meet the performance requirements of lithium-ion batteries. Lithium bis(fluorosulfonyl)imide (LiFSI) is a new type of lithium salt with excellent performance. As the main salt of electrolyte, it has the advantages of high conductivity, high chemical stability and high thermal stability. It is more in line with the future development direction of lithium batteries with high energy density, high power density and high safety. It is also one of the best choices to replace LiPF6. At the same time, LiFSI also shows great advantages when used as an additive.

[0003] But in high voltage battery system, FSI in LiFSI - Ions will cause certain corrosion to aluminum foil, which may affect the performance and life of lithium-ion batteries, and also limit the commercial application of LiFSI to a certain extent. Summary of the invention

[0004] The present invention proposes a lithium ion battery electrolyte and application thereof. The lithium ion battery electrolyte and application thereof provided by the present invention can effectively prevent corrosion of the aluminum foil current collector, improve the cycle performance of the lithium ion battery, and enhance the fast charging performance of the battery.

[0005] In order to solve the above technical problems, the present invention provides a lithium ion battery electrolyte, comprising at least the following components:

[0006] Non-aqueous solvents;

[0007] a lithium salt comprising lithium bis(fluorosulfonyl)imide; and

[0008] The additives include a first additive including diethyl cyanomethyl phosphate.

[0009] In one embodiment of the present invention, the content of the first additive in the electrolyte is 0.1 wt % to 3 wt %.

[0010] In one embodiment of the present invention, the content of the first additive in the electrolyte is 0.5 wt % to 1 wt %.

[0011] In one embodiment of the present invention, the additive includes a second additive, the second additive includes lithium tetrafluoroborate, and the content of the second additive in the electrolyte is 0.2 wt % to 3 wt %.

[0012] In one embodiment of the present invention, the mass ratio of the second additive to the first additive is 1.2:1 to 2.5:1. In one embodiment of the present invention, the mass ratio of the second additive to the first additive is 2:1 to 2.5:1.

[0013] In one embodiment of the present invention, the lithium salt further comprises lithium hexafluorophosphate, the content of the lithium bis(fluorosulfonyl)imide in the electrolyte is 3wt% to 6wt%, and the total content of the lithium bis(fluorosulfonyl)imide and the lithium hexafluorophosphate in the electrolyte is 13wt% to 16wt%.

[0014] In one embodiment of the present invention, the non-aqueous solvent includes carbonate, and the carbonate is selected from at least one of ethylene carbonate, propylene carbonate, dimethyl carbonate, ethyl methyl carbonate, or diethyl carbonate.

[0015] In one embodiment of the present invention, the non-aqueous solvent further comprises carboxylate, the carboxylate is selected from at least one of methyl acetate and ethyl acetate, and the content of the carboxylate in the electrolyte is 10 wt % to 20 wt %.

[0016] The present invention also provides a lithium ion battery, comprising at least:

[0017] A positive electrode sheet, comprising a positive electrode current collector and a positive electrode active layer disposed at least on one side of the positive electrode current collector, wherein the positive electrode active layer comprises a positive electrode active material, and the positive electrode active material comprises a nickel-cobalt-manganese ternary positive electrode active material;

[0018] A negative electrode; and

[0019] The electrolyte is selected from the lithium-ion battery electrolyte described above.

[0020] The present invention also provides an electronic device, comprising the lithium-ion battery described above.

[0021] In summary, the present invention proposes a lithium-ion battery electrolyte and its application, which can prevent the dissolution of transition metal ions in the positive electrode active material under high temperature and high pressure conditions, and improve the high temperature cycle performance of the battery. It can effectively prevent the corrosion of LiFSI on the aluminum foil current collector, and further improve the long cycle life of the lithium-ion battery. By using the first additive in combination with the second additive, the DC impedance of the lithium-ion battery is effectively reduced, and the fast charging performance is improved. By using lithium bis(fluorosulfonyl)imide and lithium hexafluorophosphate together, the chemical stability and thermal stability of the lithium-ion battery can be improved, the cycle performance of the lithium-ion battery can be improved, the conductivity of the electrolyte is improved, and the fast charging performance of the battery is further improved. DETAILED DESCRIPTION

[0022] The following describes the embodiments of the present invention through specific examples, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention.

[0023] It should be understood that the present invention can be implemented in different forms and should not be interpreted as limited to the embodiments set forth herein. On the contrary, these embodiments are provided to make the disclosure thorough and complete and to fully convey the scope of the present invention to those skilled in the art.

[0024] The technical scheme of the present invention is further described in detail below in conjunction with the embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0025] The present invention proposes a lithium-ion battery, which is, for example, a primary battery or a secondary battery, and the secondary battery is, for example, a soft-pack battery, a square-shell battery or a cylindrical battery, etc. The present invention does not specifically limit the type of lithium-ion battery. In one embodiment of the present invention, the lithium-ion battery includes a shell and a bare cell disposed in the shell, and the bare cell includes a positive electrode sheet, a separator and a negative electrode sheet. The positive electrode sheet, the separator and the negative electrode sheet are stacked in sequence to ensure that a separator is provided between any positive electrode sheet and any negative electrode sheet, and a multi-layer laminate is obtained by winding or folding, and is loaded into a battery shell as a bare cell. Finally, an electrolyte is injected into the shell once or multiple times so that the bare cell is completely immersed in the electrolyte.

[0026] In one embodiment of the present invention, the positive electrode sheet includes a positive current collector and a positive active layer coated on at least one surface of the positive current collector. The positive current collector is, for example, a foil formed by surface treatment of nickel, titanium, aluminum, silver, stainless steel or carbon. In addition to the foil, the positive current collector can also be used in any one or more combinations of various forms such as film, mesh, porous, foam or non-woven fabric. The thickness of the positive current collector is, for example, 8μm to 15μm. In this embodiment, the positive current collector is, for example, aluminum foil, and the thickness of the aluminum foil is, for example, 13μm.

[0027] In one embodiment of the present invention, the positive electrode active layer includes a positive electrode active material, a binder, and a conductive agent. The positive electrode active material includes, for example, a nickel-cobalt-manganese ternary positive electrode active material (NCM). The chemical formula of the nickel-cobalt-manganese ternary positive electrode active material is, for example, LiNi a Co b Mn 1-a-bO₂, where 0 < a < 1.0, 0 < b < 0.5, 0 < a + b < 1.0. In another embodiment of the present invention, the chemical formula of the nickel-cobalt-manganese ternary cathode active material is, for example, Li x [Ni y Co z Mn t M (1-y-z-t) O 2-δ , where M is selected from one or more of Cr, Zr, Ca, Mg, Cu, Ti, Al, Mo, W, Zn, etc., 0.9 < x < 1.1, 0 < x < 1.0, 0 < y < 0.5, 0 < y + z + t < 1.0, 0 ≤ δ ≤ 0.1. The binder is, for example, selected from any one or more of polyvinylidene fluoride (PVDF), poly(ethylene oxide) (PEO), polyamide (PA), polyacrylonitrile (PAN), polyacrylate, polyvinylether, polymethyl methacrylate (PMMA), ethylene-propylene-diene terpolymer (EPDM), polyhexafluoropropylene (PHFP), or polymerized styrene butadiene rubber (SBR), etc. The conductive agent is, for example, selected from any one or more of super P, acetylene black, carbon nanotubes, and graphene, etc. In the cathode active layer, the mass ratio of the cathode active material, the conductive agent, and the binder is, for example, (90-98):(1-5):(1-5).

[0028] In one embodiment of the present invention, the cathode active material is, for example, LiNi 0.6 Mn 0.2 Co 0.2 O₂, the binder is, for example, selected from polyvinylidene fluoride, and the conductive agent is, for example, selected from super P. After mixing the cathode active material, the conductive agent, and the binder according to a mass ratio of 98:1:1, an organic solvent is added, and the mixture is stirred in a vacuum mixer until the system becomes homogeneous to obtain the cathode slurry. Among them, the organic solvent is, for example, selected from N-methylpyrrolidone (NMP). The cathode slurry is uniformly coated on the aluminum foil current collector, then air-dried at room temperature and transferred to an oven for drying, and the cathode electrode sheet is obtained through processes such as cold pressing and slitting. In other embodiments, the cathode electrode sheet can also be obtained by any other method of forming the cathode electrode sheet.

[0029] In an embodiment of the present invention, the negative electrode sheet includes, for example, a negative electrode current collector and a negative electrode active layer coated at least on one surface of the negative electrode current collector. The negative electrode current collector is selected from, for example, a copper foil current collector, a composite copper foil current collector, a carbon current collector, a copper foam current collector, or a stainless steel current collector, etc. The thickness of the negative electrode current collector is, for example, 8 μm to 15 μm. In this embodiment, the negative electrode current collector is, for example, a copper foil, and the thickness of the copper foil is, for example, 13 μm.

[0030] In an embodiment of the present invention, the negative electrode active layer includes a negative electrode active material, a conductive agent, a binder, a thickening agent, etc. Among them, the negative electrode active material is a compound capable of intercalating and deintercalating lithium ions. In an embodiment of the present invention, the negative electrode active material includes, for example, graphite, silicon oxide material (SiO x , 0 < x < 2) or silicon-carbon material, etc. When the negative electrode active material includes a silicon oxide material or a silicon-carbon material, the mass ratio thereof to graphite is, for example, 2:98 to 10:90. The binder is selected from, for example, any one or more of polyvinylidene fluoride, polyethylene oxide, polyamide, polypropylene, polyacrylate, polyethylene ether, polymethyl methacrylate, polyhexafluoropropylene, or styrene-butadiene rubber, etc. The thickening agent is, for example, carboxymethyl cellulose sodium (CMC-Na), etc., and the conductive agent is selected from, for example, any one or more of conductive carbon black, acetylene black, Ketjen black, carbon nanotubes, and graphene, etc. The mass ratio of the negative electrode active material, the conductive agent, the binder, and the thickening agent in the negative electrode active layer is, for example, (90 to 96):(1 to 2):(1 to 3):(2 to 5).

[0031] In an embodiment of the present invention, the negative electrode active material is selected from, for example, graphite and silicon oxide material, and the mass ratio of the silicon oxide material to graphite is, for example, 5:95. The conductive agent is selected from, for example, conductive carbon black, and the thickening agent is selected from, for example, carboxymethyl cellulose sodium, and the binder is selected from, for example, styrene-butadiene rubber. In an embodiment of the present invention, the negative electrode active material, the conductive agent, the binder, and the thickening agent are, for example, mixed according to a mass ratio of 96:1:1:2, deionized water is added, and the mixture is uniformly mixed under the action of a vacuum mixer to obtain a negative electrode slurry. The negative electrode slurry is coated on the copper foil, and then dried at room temperature and transferred to an oven for drying. After cold pressing and slitting and other processes, a negative electrode sheet is obtained. In other embodiments, the negative electrode sheet can also be obtained by selecting any other method for forming a negative electrode sheet.

[0032] In one embodiment of the present invention, the diaphragm is, for example, a polyethylene film (PE), a polypropylene film (PP), a glass fiber film or a composite film, and the thickness of the diaphragm is, for example, 9 μm to 15 μm. In one embodiment of the present invention, the diaphragm is, for example, a polyethylene of 8 μm to 10 μm as a base film, and a nano-aluminum oxide coating with a thickness of 2 μm to 4 μm is coated on the base film to obtain the diaphragm.

[0033] In one embodiment of the present invention, the lithium-ion battery also includes an electrolyte injected into and filling the entire internal space of the battery. The positive electrode plate, the separator and the negative electrode plate are completely immersed in the electrolyte. The electrolyte plays the role of conducting ions, providing ion channels and maintaining chemical stability. The various components in the electrolyte can be divided into non-aqueous solvents, lithium salts and additives according to their functions and addition amounts. The non-aqueous solvent is used to dissolve the lithium salts and additives; the lithium salt is mainly used to provide lithium ions to form ion channels; in the entire electrochemical system of the battery, the directional movement of lithium ions and electrons generates electricity. The lithium salt has a great influence on the energy density, power density, wide electrochemical window, cycle life and safety performance of the lithium battery. Additives are substances added in small amounts to the electrolyte. There are many types and each plays a different role. For example, they can have different improvement effects on the high and low temperature performance, cycle performance, film forming performance, etc. of the battery.

[0034] The present invention provides a lithium ion battery electrolyte, which comprises at least a non-aqueous solvent, a lithium salt and an additive, wherein the additive comprises a first additive and a second additive, and the first additive comprises diethyl cyanomethyl phosphate (C6H 12 NO3P), etc., and the second additive includes lithium tetrafluoroborate (LiBF4), etc. Diethyl cyanomethyl phosphate forms a uniform cathode-electrolyte interface (Catheode Electrolyte Inter Phase, CEI) at the interface where the positive electrode contacts the electrolyte to protect the positive electrode active material, prevent the dissolution of transition metal ions in the positive electrode active material under high temperature and high pressure conditions, and improve the high temperature cycle performance of lithium-ion batteries. In addition, the first additive can also effectively prevent LiFSI from corroding the aluminum foil current collector, further improving the long cycle life of lithium-ion batteries. When the first additive is used in combination with the second additive LiBF4, the direct current resistance (DCR) of the lithium-ion battery can be effectively reduced, and the fast charging performance can be improved.

[0035] In one embodiment of the present invention, the content of the first additive in the electrolyte is, for example, 0.1wt% to 3wt%, and for example, 0.5wt% to 1wt%. The content of the second additive in the electrolyte is, for example, 0.2wt% to 3wt%, and the mass ratio of the second additive to the first additive is, for example, 1.2:1 to 2.5:1. Further, the mass ratio of the second additive to the first additive is, for example, 2:1 to 2.5:1. If the content of the first additive is too low, the stability of the formed CEI film is poor and the gas production performance is poor. If the content of the first additive is too high, the thickness of the CEI film is too thick, and the DC impedance of the lithium-ion battery is large, which is not conducive to the battery capacity. Controlling the content of the second additive can simultaneously optimize multiple properties of the lithium-ion battery. Therefore, the content and ratio of the first additive and the second additive are controlled to achieve the purpose of protecting the positive electrode collector, improving the fast charging performance, and improving the cycle performance.

[0036] In one embodiment of the present invention, the lithium salt includes at least lithium bis(fluorosulfonyl)imide, and the fluorine ions in the structure of lithium bis(fluorosulfonyl)imide have strong electron-withdrawing properties, which weakens the coordination effect between anions and cations in the lithium salt, making the activity of lithium ions stronger, thereby improving the conductivity of the electrolyte and further improving the fast charging performance of the battery. In this embodiment, the lithium salt also includes lithium hexafluorophosphate, etc., and the content of lithium bis(fluorosulfonyl)imide in the electrolyte is 3wt% to 6wt%, and the total content of lithium bis(fluorosulfonyl)imide and lithium hexafluorophosphate in the electrolyte is 13wt% to 16wt%. By sharing lithium bis(fluorosulfonyl)imide and lithium hexafluorophosphate, the problem of corrosion of aluminum foil current collector caused by using a single lithium bis(fluorosulfonyl)imide can be avoided. At the same time, the total content of lithium salt is controlled. If the total content of lithium salt is too small, the fast charging performance of the lithium ion battery is poor and lithium precipitation is easy. If the total content of lithium salt is too large, the number of solvated lithium ions will be reduced, the ionic conductivity of the electrolyte will be reduced, and the fast charging performance will be affected. Therefore, by using lithium bis(fluorosulfonyl)imide and lithium hexafluorophosphate together, the chemical stability and thermal stability of lithium-ion batteries can be improved, the cycle performance of lithium-ion batteries can be improved, and the corrosion of the positive electrode current collector can be reduced while improving the fast charging performance of lithium-ion batteries.

[0037] In one embodiment of the present invention, the non-aqueous solvent includes, for example, carbonate, which is selected from at least one of ethylene carbonate (EC), propylene carbonate (PC), dimethyl carbonate (DMC), ethyl methyl carbonate (EMC) or diethyl carbonate (DEC). The non-aqueous solvent also includes, for example, carboxylic acid ester, which is selected from at least one of methyl acetate (MA) or ethyl acetate (EA). The content of carboxylic acid ester in the electrolyte is 10wt% to 20wt%. By adding appropriate carboxylic acid ester to the electrolyte, a synergistic effect can be formed with the electrolyte additive to further improve the fast charging performance of the lithium-ion battery.

[0038] In one embodiment of the present invention, when preparing the electrolyte, in a glove box with an inert gas atmosphere such as argon with a moisture content of less than or equal to 0.1 ppm, after the non-aqueous solvent is uniformly mixed according to the mass ratio, the fully dried lithium salt is added to the non-aqueous solvent, and the additive is added to prepare the lithium ion battery electrolyte. The content described in this application is the weight percentage calculated based on the total weight of the electrolyte.

[0039] In one embodiment of the present invention, the positive electrode sheet, the separator, and the negative electrode sheet are placed in sequence, so that the separator is located between the positive electrode sheet and the negative electrode sheet to play an isolating role, and a bare cell is obtained by winding or laminating. The bare cell is placed in a shell, dried in a vacuum oven, and sealed after injecting the electrolyte prepared in the present application, and at least undergoes the processes of standing, forming, and volume separation to obtain a lithium-ion battery.

[0040] Hereinafter, the present invention will be explained in more detail by citing examples, which should not be construed as limiting. Appropriate modifications may be made within the scope consistent with the gist of the present invention, all of which fall within the technical scope of the present invention.

[0041] Example 1

[0042] Preparation of electrolyte: In an argon glove box with a moisture content of less than 0.1 ppm, ethylene carbonate, dimethyl carbonate and ethyl methyl carbonate are mixed uniformly in a mass ratio of 3:5:2 to obtain a mixed solvent, and then carboxylic acid ester methyl acetate, lithium hexafluorophosphate, lithium bisfluorosulfonyl imide and the first additive diethyl cyanomethyl phosphate are added to the mixed solvent, and the electrolyte is obtained after mixing uniformly. In the obtained electrolyte, the content of methyl acetate is 10wt%, the content of lithium hexafluorophosphate is 12wt%, the content of lithium bisfluorosulfonyl imide is 4wt%, and the content of diethyl cyanomethyl phosphate is 0.5wt%.

[0043] Preparation of positive electrode: LiNi 0.6 Mn 0.2 Co 0.2 After mixing O2, polyvinylidene fluoride and conductive carbon black in a mass ratio of 98:1:1, N-methylpyrrolidone was added and stirred in a vacuum mixer until the system was uniform to obtain a positive electrode slurry. The positive electrode slurry was evenly coated on the aluminum foil current collector, then dried at room temperature and transferred to an oven for drying, and the positive electrode sheet was obtained through cold pressing and slitting processes.

[0044] Preparation of negative electrode sheet: The negative electrode active materials are graphite and silicon oxide materials, and the mass ratio of silicon oxide materials to graphite is 5:95. The negative electrode active materials, conductive carbon black, sodium carboxymethyl cellulose and styrene butadiene rubber are mixed in a mass ratio of 96:1:1:2, deionized water is added, and mixed evenly under the action of a vacuum mixer to obtain negative electrode slurry. The negative electrode slurry is coated on copper foil, and then transferred to an oven for drying after drying at room temperature, and the negative electrode sheet is obtained after cold pressing and slitting processes.

[0045] Selection of diaphragm: Use 12μm thick polypropylene diaphragm.

[0046] Preparation of battery: The positive electrode sheet, separator, and negative electrode sheet are wound in sequence, and the separator is placed between the positive electrode sheet and the negative electrode sheet to play an isolating role, thereby obtaining a bare cell. The bare cell is then placed in a shell, dried in a vacuum oven, and then the above-prepared electrolyte is injected and sealed, and a formation process is performed to obtain a lithium-ion battery.

[0047] Example 2

[0048] In the electrolyte, the carboxylic acid ester includes methyl acetate and ethyl acetate, the content of methyl acetate is 10wt%, the content of ethyl acetate is 5wt%, and the other steps are consistent with Example 1.

[0049] Example 3

[0050] In the electrolyte, the carboxylic acid ester includes methyl acetate and ethyl acetate, the content of methyl acetate is 10wt%, the content of ethyl acetate is 10wt%, and the other steps are consistent with Example 1.

[0051] Example 4

[0052] In the electrolyte, the carboxylic acid ester includes methyl acetate and ethyl acetate, the content of methyl acetate is 10wt%, the content of ethyl acetate is 5wt%, the content of lithium hexafluorophosphate is 10wt%, the content of lithium bis(fluorosulfonyl)imide is 6wt%, and the other steps are consistent with Example 1.

[0053] Example 5

[0054] In the electrolyte, the carboxylic acid ester includes methyl acetate and ethyl acetate, the content of methyl acetate is 10wt%, the content of ethyl acetate is 5wt%, the content of diethyl cyanomethyl phosphate is 0.1wt%, and the other steps are consistent with Example 1.

[0055] Example 6

[0056] In the electrolyte, the carboxylic acid ester includes methyl acetate and ethyl acetate, the content of methyl acetate is 10wt%, the content of ethyl acetate is 5wt%, the content of diethyl cyanomethyl phosphate is 1wt%, and the other steps are consistent with Example 1.

[0057] Example 7

[0058] In the electrolyte, the carboxylic acid ester includes methyl acetate and ethyl acetate, the content of methyl acetate is 10wt%, the content of ethyl acetate is 5wt%, the content of diethyl cyanomethyl phosphate is 3wt%, and the other steps are consistent with Example 1.

[0059] Example 8

[0060] In the electrolyte, carboxylic acid ester is not included, and the other steps are consistent with Example 1.

[0061] Example 9

[0062] In the electrolyte, the carboxylic acid ester includes methyl acetate and ethyl acetate, the content of methyl acetate is 15wt%, the content of ethyl acetate is 15wt%, and the other steps are consistent with Example 1.

[0063] Example 10

[0064] In the electrolyte, the carboxylic acid ester includes methyl acetate and ethyl acetate, the content of methyl acetate is 10wt%, the content of ethyl acetate is 5wt%, the content of lithium hexafluorophosphate is 13wt%, the content of lithium bis(fluorosulfonyl)imide is 3wt%, and the other steps are consistent with Example 1.

[0065] Embodiment 11

[0066] In the electrolyte, the carboxylic acid ester includes methyl acetate and ethyl acetate, the content of methyl acetate is 10wt%, the content of ethyl acetate is 5wt%, the content of lithium hexafluorophosphate is 13.5wt%, the content of lithium bis(fluorosulfonyl)imide is 2.5wt%, and the other steps are consistent with Example 1.

[0067] Example 12

[0068] In the electrolyte, the carboxylic acid ester includes methyl acetate and ethyl acetate, the content of methyl acetate is 10wt%, the content of ethyl acetate is 5wt%, the positive electrode active material is changed to LiCoO2 (LCO), and the other steps are consistent with Example 1.

[0069] Embodiment 13

[0070] In the electrolyte, the carboxylic acid ester includes methyl acetate and ethyl acetate, the content of methyl acetate is 10wt%, the content of ethyl acetate is 5wt%, and the second additive LiBF4 is added at the same time, the content of LiBF4 is 0.6wt%, and the other steps are consistent with Example 1.

[0071] Embodiment 14

[0072] In the electrolyte, the content of LiBF4 is 1 wt %, and the other steps are consistent with Example 13.

[0073] Embodiment 15

[0074] In the electrolyte, the content of LiBF4 is 1.25wt%, and the other steps are consistent with Example 13.

[0075] Example 16

[0076] In the electrolyte, the content of LiBF4 is 1.5wt%, and the other steps are consistent with Example 13.

[0077] Comparative Example 1

[0078] The electrolyte does not include diethyl cyanomethyl phosphate, and the other steps are consistent with those in Example 2.

[0079] Comparative Example 2

[0080] In the electrolyte, the first additive diethyl cyanomethyl phosphate was replaced with diethyl 3-cyanophenyl phosphate, the content of diethyl 3-cyanophenyl phosphate was 0.5 wt %, and the other steps were consistent with Example 2.

[0081] Comparative Example 3

[0082] In the electrolyte, the first additive diethyl cyanomethyl phosphate was replaced with diethyl 4-cyanobenzyl phosphite, the content of diethyl 4-cyanobenzyl phosphite was 0.5 wt %, and the other steps were consistent with Example 2.

[0083] Comparative Example 4

[0084] The positive electrode active material was changed to LiCoO2, and diethyl cyanomethyl phosphate was not added to the electrolyte. The other steps were consistent with Example 2.

[0085] In the present invention, in Examples 1-16 and Comparative Examples 1-4, the components and systems of the electrolyte in the lithium ion battery are shown in Table 1, and different electrolytes or positive electrode active materials are used to prepare lithium ion batteries, and the performance of the lithium ion batteries is tested, and the test results are shown in Tables 2 and 3.

[0086] In one embodiment of the present invention, a fast charge cycle lithium plating test (ALP) is a fast charge cycle test that measures the fast charge capability of a battery. Under different states of charge (SOC), different rates are used for charge and discharge. For example, a fast charge cycle test is performed on a lithium-ion battery using a charge and discharge regime of 3% to 10% SOC-1C, 10% to 30% SOC-4C, 30% to 50% SOC-3C, 50% to 70% SOC-2.5C, 70% to 80% SOC-2C, and 80% to 97% SOC-1C. After 20 cycles (cls), the battery cell is disassembled to observe the lithium plating condition of the negative electrode.

[0087] In one embodiment of the present invention, the DCR test at 25°C is to place the lithium-ion battery in a thermostat, adjust the thermostat temperature to 25°C, let it stand for 10 minutes, charge it to 4.4V at a constant current of 0.33C, then charge it to 0.05C at a constant voltage of 4.4V, let it stand for 30 minutes, and then discharge it to 2.8V at a constant current of 0.33C. Repeat the cycle twice, and record the last discharge capacity as C0. After standing for 30 minutes, discharge it to 50% C0 at 0.33C, adjust the battery cell SOC to 50%, let it stand for 30 minutes, record the static terminal voltage V1, and then discharge it at a constant current of 4C0 for 30 seconds, record the terminal voltage V2 and current I, and calculate DCR = (V1-V2) / I.

[0088] In one embodiment of the present invention, the gas production growth rate test after 500 cycles at 45°C is to place the lithium-ion battery in a constant temperature box, adjust the temperature of the constant temperature box to 45°C, perform cyclic charge and discharge at a current of 1C in the potential range of 2.8V to 4.4V, and record the gas production growth rate after 500 cycles.

[0089] In one embodiment of the present invention, the 60°C high temperature storage for 30 days corrosion test is to charge the lithium-ion battery to 4.4V at 0.33C constant current at 25°C, then charge it to 0.05C at constant voltage, and let it stand for 30 minutes. Then, the fully charged battery is placed in a 60°C oven for 30 days. The battery cell is cooled, and after the battery cell is disassembled, the corrosion of the aluminum foil current collector is observed and recorded using a laser microscope.

[0090] In one embodiment of the present invention, the fast charge cycle capacity retention rate test is carried out in an environment of 25°C, with the charge and discharge voltage set to 2.8V~4.4V, the charging current density to 3C, the discharge current density to 1C, the cut-off current to 0.05C, and the above process is followed for 200 cycles, and the fast charge cycle capacity retention rate is obtained by the discharge capacity at the 200th cycle / the discharge capacity at the 1st cycle.

[0091] Table 1. Electrolyte and battery system in Examples 1-16 and Comparative Examples 1-4

[0092]

[0093] Table 2 Performance test results of lithium ion batteries in Examples 1-16 and Comparative Examples 1-4

[0094]

[0095] Table 3. Fast charging performance test results of lithium-ion batteries in Examples 1, 2, 4, 10, and 11

[0096] Group Fast charge cycle capacity retention rate (200 cycles) Example 1 94.1% Example 2 94.1% Example 4 94.8% Example 10 92.7% Embodiment 11 87.4%

[0097] Please refer to Table 1 and Table 2. By comparing Examples 1, 5-7 and Comparative Example 1, it can be seen that when the first additive is added to the electrolyte and the content of the first additive is in the range of 0.1wt% to 3wt%, the fast charging performance and high temperature cycle gas production performance of the lithium ion battery can be well balanced, and the aluminum foil current collector can be effectively prevented from corrosion. Furthermore, when the content of the first additive is in the range of 0.5wt% to 1wt%, the comprehensive performance of the lithium ion battery is good.

[0098] Please refer to Table 1 and Table 2. By comparing Examples 1-3 and Examples 8-9, it can be seen that when carboxylates are not added to the electrolyte, the DC impedance, fast charging and cycle performance of the lithium-ion battery will deviate. Carboxylates are added to the electrolyte and the total content is controlled at 10wt% to 20wt%. Within this range, the introduction of carboxylates can reduce the DC impedance of the lithium-ion battery, improve the fast charging performance of the lithium-ion battery, and improve gas production. However, when the amount of carboxylates exceeds this range, it will cause serious gas production during high-temperature cycling of the battery, so the amount of carboxylates needs to be controlled.

[0099] Please refer to Table 1, Table 2 and Table 3. By comparing Examples 1, 4, 10-11, it can be seen that the total content of lithium salt in the electrolyte is 16wt%, and the content of LiFSI is changed. As the content of LiFSI increases, the fast charge cycle capacity retention rate increases, and the fast charge cycle performance improves, but too much will cause more gas production. Therefore, the content of LiFSI is controlled to ensure that the comprehensive performance of the lithium ion battery is better. By comparing Example 2 and Examples 13-16, it can be seen that when the first additive and the second additive are used simultaneously at a specific content, the DC impedance of the lithium ion battery is reduced, lithium precipitation does not occur, and the cycle gas production performance is improved. At the same time, the aluminum foil current collector is not corroded, and the performance of the lithium ion battery is further optimized. By comparing Examples 2 and 12 with Comparative Example 4, it can be seen that when the positive electrode active material is lithium cobalt oxide, adding the first additive diethyl cyanomethyl phosphate to the electrolyte can also effectively inhibit the corrosion of the aluminum foil current collector, improve the fast lithium charging and precipitation, and reduce the DC impedance and gas production of the positive electrode active material system. However, compared with the nickel-cobalt-manganese ternary positive electrode active material system, the DC impedance of the lithium-ion battery is higher and the gas production is serious. Therefore, diethyl cyanomethyl phosphate has a better improvement effect on the battery of the nickel-cobalt-manganese ternary positive electrode active material system.

[0100] Please refer to Table 1 and Table 2. By comparing Example 6 with Comparative Examples 7-8, it can be seen that 3-cyanophenyl diethyl phosphate and 4-cyanobenzyl diethyl phosphite also have cyano and phosphate groups, but cannot inhibit the corrosion of the aluminum foil current collector. Therefore, the first additive with a specific structure is selected to inhibit the corrosion of the aluminum foil current collector.

[0101] The present invention also provides an electronic device, the electronic device includes at least one of the above-mentioned lithium-ion batteries, and the lithium-ion battery is used to provide electrical energy. Among them, the electronic device can be a vehicle, a mobile phone, a portable device, a laptop computer, a ship, a spacecraft, an electric toy and an electric tool, etc. In one embodiment of the present invention, the vehicle is, for example, a new energy vehicle, and the new energy vehicle can be a pure electric vehicle, a hybrid vehicle or an extended-range vehicle, etc. Spacecraft include airplanes, rockets, space shuttles and spacecrafts, etc. Electric toys include fixed or mobile electric toys, such as game consoles, electric car toys, electric ship toys and electric airplane toys, etc. Electric tools include metal cutting electric tools, grinding electric tools, assembly electric tools and railway electric tools, such as electric drills, electric grinders, electric wrenches, electric screwdrivers, electric hammers, impact drills, concrete vibrators and electric planers, etc. The electronic device includes the above-mentioned lithium-ion battery, so the advantages of the above-mentioned lithium-ion battery are included, which will not be elaborated here.

[0102] In summary, the present invention proposes a lithium-ion battery electrolyte and its application. By adding a first additive, the dissolution of transition metal ions in the positive electrode active material under high temperature and high pressure conditions can be prevented, thereby improving the high temperature cycle performance of the battery. It can effectively prevent the corrosion of LiFSI to the aluminum foil current collector, further improving the long cycle life of the lithium-ion battery. By using the first additive in combination with the second additive, the DC impedance of the lithium-ion battery is effectively reduced, and the fast charging performance is improved. By using lithium bis(fluorosulfonyl)imide and lithium hexafluorophosphate together, the chemical stability and thermal stability of the lithium-ion battery can be improved, the cycle performance of the lithium-ion battery can be improved, the conductivity of the electrolyte can be improved, and the fast charging performance of the battery can be further improved.

[0103] The above description is only a preferred embodiment of the present application and an explanation of the technical principles used. Those skilled in the art should understand that the scope of the invention involved in the present application is not limited to the technical solution formed by a specific combination of the above-mentioned technical features, but should also cover other technical solutions formed by any combination of the above-mentioned technical features or their equivalent features without departing from the inventive concept, such as a technical solution formed by replacing the above-mentioned features with (but not limited to) technical features with similar functions disclosed in this application.

[0104] Except for the technical features described in the specification, the remaining technical features are known technologies to those skilled in the art. In order to highlight the innovative features of the present invention, the remaining technical features will not be described here in detail.

Claims

1. A lithium ion battery electrolyte, characterized in that: At least the following components are included: Non-aqueous solvents; a lithium salt comprising lithium bis(fluorosulfonyl)imide; and The additives include a first additive including diethyl cyanomethyl phosphate.

2. The lithium ion battery electrolyte according to claim 1, characterized in that: The content of the first additive in the electrolyte is 0.1 wt% to 3 wt%.

3. The lithium ion battery electrolyte according to claim 1, characterized in that The content of the first additive in the electrolyte is 0.5 wt % to 1 wt %.

4. The lithium ion battery electrolyte according to claim 1, characterized in that: The additive includes a second additive, the second additive includes lithium tetrafluoroborate, and the content of the second additive in the electrolyte is 0.2 wt % to 3 wt %.

5. The lithium ion battery electrolyte according to claim 4, characterized in that: The mass ratio of the second additive to the first additive is 1.2:1 to 2.5:

1.

6. The lithium ion battery electrolyte according to claim 1, characterized in that: The lithium salt further comprises lithium hexafluorophosphate, the content of the lithium bis(fluorosulfonyl)imide in the electrolyte is 3wt% to 6wt%, and the total content of the lithium bis(fluorosulfonyl)imide and the lithium hexafluorophosphate in the electrolyte is 13wt% to 16wt%.

7. The lithium ion battery electrolyte according to claim 1, characterized in that: The non-aqueous solvent includes carbonate, and the carbonate is selected from at least one of ethylene carbonate, propylene carbonate, dimethyl carbonate, ethyl methyl carbonate, or diethyl carbonate.

8. The lithium ion battery electrolyte according to claim 1, characterized in that: The non-aqueous solvent further comprises carboxylate, and the carboxylate is selected from at least one of methyl acetate and ethyl acetate, and the content of the carboxylate in the electrolyte is 10 wt % to 20 wt %.

9. A lithium ion battery, characterized in that: At least: A positive electrode sheet, comprising a positive electrode current collector and a positive electrode active layer disposed at least on one side of the positive electrode current collector, wherein the positive electrode active layer comprises a positive electrode active material, and the positive electrode active material comprises a nickel-cobalt-manganese ternary positive electrode active material; A negative electrode; and An electrolyte, wherein the electrolyte is selected from the lithium ion battery electrolyte according to any one of claims 1 to 8.

10. An electronic device, characterized in that: Includes the lithium ion battery as claimed in claim 9.

Citation Information

Patent Citations

  • Capacitance-lithium ion secondary battery

    CN103378383A

  • Electrolyte solution lithium and secondary battery containing electrolyte solution

    CN106848381A

  • Secondary battery, method for manufacturing secondary battery, battery module, battery pack, and power device

    CN116111178A

  • Nonaqueous electrolyte and nonaqueous electrolyte battery including the same

    JP2013065540A

  • Additive for nonaqueous electrolyte, nonaqueous electrolyte and electricity storage device

    JP2013175426A